Information asymmetry, valuation, and the corporate spin-off decision - Krishnaswami, Sudha; Subramaniam, Venkat (Journal of Financial Economics, 1999)
We empirically analyze the information hypothesis that the separation of a firm's divisions into independently traded units through a spin-off enhances value because it mitigates information asymmetry about the firm. Consistent with this hypothesis, we find that firms that engage in spin-offs have higher levels of information asymmetry compared to their industry and size matched counterparts and the information problems decrease significantly after the spin-off. The gains around spin-offs are positively related to the degree of information asymmetry, and this relation is more pronounced for firms with fewer negative synergies between divisions. Finally, firms with higher growth opportunities and firms in need of external capital show a higher propensity to engage in spin-offs. They also raise more capital following a spin-off, which is consistent with the view that these firms mitigate information asymmetry before approaching the capital market for funds.